2020
DOI: 10.1039/d0dt02414g
|View full text |Cite
|
Sign up to set email alerts
|

Systematic spectroscopic investigation of structural changes and corona formation of bovine serum albumin over magneto-fluorescent nanoparticles

Abstract: Magneto-fluorescent nanoparticles have spellbound great attention because of their dual nature as an multimodal imaging probe in various biomedical applications. Particulary, it is desirable to understand how these nanoparticles interact...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…33 These materials showed superior MR imaging, bioimaging, uorescence sensing, hyperthermia and targeted drug delivery. [34][35][36][37] Extending the possibility of core-shell SPIONs in opto-electronic applications, we attempted to incorporate nitrogen in core-shell SPIONs using our established protocol. We used a nitrogen-based precursor and the synthesized nitrogen doped carbon coated core-shell SPIONs by optimizing the precursor concentration as detailed in Table S1 in the ESI.…”
Section: One Step Synthesis Method Magnetic Separation and Nanopartic...mentioning
confidence: 99%
“…33 These materials showed superior MR imaging, bioimaging, uorescence sensing, hyperthermia and targeted drug delivery. [34][35][36][37] Extending the possibility of core-shell SPIONs in opto-electronic applications, we attempted to incorporate nitrogen in core-shell SPIONs using our established protocol. We used a nitrogen-based precursor and the synthesized nitrogen doped carbon coated core-shell SPIONs by optimizing the precursor concentration as detailed in Table S1 in the ESI.…”
Section: One Step Synthesis Method Magnetic Separation and Nanopartic...mentioning
confidence: 99%
“…Fortunately, significant progress is being made in characterizing the nanoparticle corona as a function of nanomaterials physicochemical properties and the environment in which they are found. A number of studies in the past year have reported a range of spectroscopic, mass spectrometric, and chromatographic methods for characterizing nanoparticle coronas, some of which can be used to study the dynamic properties of biocoronas (figure 4) [78][79][80][81][82][83][84][85][86][87]. These data have enabled development of explanatory and potentially predictive models of nanoparticle corona composition [88][89][90][91][92][93] and dynamic behaviour that form the basis for rational design and development of nanomaterials that attract little or no corona [94].…”
Section: Descriptionmentioning
confidence: 99%
“…When nanoparticles with high specific surface and high surface charge are in biological fluids, they can interact with proteins to form a protein shell with various conformations named protein corona, which can affect their physicochemical properties and the ability to enter cells [19][20][21][29][30][31]. Thus the interaction of the selected red fractions of CDs 18.5bar , CDs 13bar and CDs 8bar with DMEM serum protein was established exploring the aggregation of them after incubation at 37 • C by DLS measurements.…”
Section: Evaluation Of Serum Protein Interactions By Dynamic Light Sc...mentioning
confidence: 99%